Effect of grilling and roasting on fatty acids methyl esthers (FAME) in beef and pork - Alina A.R.; Nurulhuda M.S.; Siti Mashitoh A.; Shazamawati Z.H.; Nurul Mawaddah A.H.; Ummi Syuhada H.S.; Nurul Farah S.A.; Nurul Aqilah A.S.; Syamsul K.M.W.; Nur Nadiah Syuhada A.S. (2024)
Indexed by Scopus